Conflicting philosophies of inclusion: the contestation of knowledge in widening participation. (1st November 2007) - Sheeran, Yanina; Brown, B. J.; Baker, Sally
Abstract : This paper explores the conflicting philosophies within the widening participation debate. Two categories of inclusive educators are identified, 'meritocrats' and 'democrats'. Among the democratic educators, a subgroup, 'transformative' educators, exists, which seeks to invoke changes in society and the education system. The positions taken by some of these authors are weakened by their neglect of sociological theory. For the debate to progress and for inclusion to be successful, a renewed understanding of sociological theory is needed. This will help those contributing to the debate to grasp fully the political and economic constraints on students and institutions that have limited inclusion.